“Efecto de tres dosis de tetrahormona en el cultivo de brócoli usando el híbrido royal favor F-1 HyB en la provincia de Lamas” - Rocha López, Juan José (2016)
The present investigation entitled "Effect of three doses of tetrahormona in growing broccoli, using the hybrid F-1 Royal Favor HyB in the province of Lamas", was aimed to evaluate and analyze bio-stimulant dose tetrahormonal efficient (Biogyz) on broccoli crops production and make economic analysis of the treatments studied. Applying Biogyz were applied at 15, 30 and 45 days after sowing, using statistical design of randomized complete block (RCBD) with four treatments and four blocks. The results indicate that treatment T3 (400 cc.ha-1 Biogyz) obtained the highest average performance 15 296,6 kg ha-1 being statistically equal to T2 (300 cc.ha-1 Biogyz) who earned a average of 13 986,3 kg ha·1 and which in turn exceeded their averages statistically the T1 (200 Biogyz cc.ha-1 ) and TO (Witness) who obtained averages 12 and 7 865,5 102.8 kg ha·1 yield respectively. Performance results obtained in kg.ha-1 determined that the yield increase was a direct function of increasing doses of tetrahormona applied and soil and climatic conditions, which is explained by the equation of the straight line defined by Y = 2 417,7X T- 6 268,6 confirming a positive linear behavior. T3 treatment (400 cc.ha·1 Biogyz) also obtained the highest average weight of the inflorescence with 626,0 g. This result also found that the weight increase of the inflorescence was a direct function of increasing doses of tetrahormona applied and explained by the equation of the straight line defined by Y= + 6 268,6 25 417,7X ratifying positive linear behavior. T3 treatment (400 cc.ha-1 Biogyz) obtained the highest average plant height of 37, 1 cm. These results defined a increase in plant height function of increasing doses of tetrahormona and explained by the equation of the straight fine defined by Y= 2,34X + 27,85 O. All treatments yielded indices B/C greater than 1. Since T3 (400 kg ha-1 ) showed the highest value to 3,69 and treatment TO (control) the lower value with an index of 1, 6 B/C. Key words: Biostimulant, tetrahormona, Biogyz, hybrid, Royal Favor F-1 HyB, dosage, treatment, blocks, performance, cost benefit. +